Effects of cigarette smoking on the response of hypertensive patients to beta-adrenergic antagonists: a narrative review (Journal of Ideas in Health, 2022)
Cigarette smoking is one of the hypertension risk factors which can adversely affect the quality of life. This review aimed to provide a brief overview of the link between smoking and hypertension. At the same time, raising questions about how smoking interacts with beta-adrenergic antagonists that are used as antihypertensive drugs. By searching for relevant studies through multiple search engines, there is inconsistent evidence about the effect of smoking on high blood pressure. Mainly attributed to the availability of numerous confounding factors. However, cigarette smoking cannot be ignored because smoking exerts dual effects on hypertension as a disease and the treatment with antihypertensive drugs, particularly beta-adrenergic antagonists. The potential drug interaction can occur through pharmacokinetics and pharmacodynamics mechanisms resulting in influencing the efficacy of these drugs. It is necessary to have dosage modifications according to the patient's smoking status, whether in hospitals or outpatient clinics.